The Effectiveness of Imtihan Culture as an Instrument for Evaluation of Student Learning Outcomes at Madrasah Diniyah Takmiliyah Awaliyah in Bungo Regency - Khamim, Siti (BiCED Proceeding, 2023)
This research aims to determine the effectiveness of imtihan culture as an instrument for evaluating student learning outcomes at Madrasah Diniyah Takmiliyah Awaliyah in Bungo Regency. Imtihan culture, a form of open examination that involves written and oral imtihan, plays an important role in instilling religious values, evaluating learning outcomes, and interaction between students, teachers and parents. Imtihan also functions as an evaluation tool for madrasah managers and motivates students. The method used is a qualitative method. The research results show that imtihan culture has a significant role in instilling religious values, evaluating learning outcomes for one year, as well as interactions between students, teachers and parents. Imtihan is not only an academic evaluation tool, but also an important moment in the community in Hamlet in the Bungo Regency area. Imtihan involves the active participation of parents in accompanying their children and being direct witnesses in the evaluation process. Apart from that, imtihan also functions as an evaluation tool for Madrasah managers and administrators, who use the results of imtihan to improve the quality of education and provide incentives to teachers. Imtihan also creates motivation for students to study hard, because they are assessed by teachers from outside their madrasah